Transcription Factor Avian Erythroblastosis Virus E26 Oncogen Homolog-1 Is a Novel Mediator of Renal Injury in Salt-Sensitive Hypertension. Issue 4 (April 2015) - Feng, Wenguang; Chumley, Phillip; Prieto, Minolfa C.; Miyada, Kayoko; Seth, Dale M.; Fatima, Huma; Hua, Ping; Rezonzew, Gabriel; Sanders, Paul W.; Jaimes, Edgar A.
<x xml:space="preserve">Abstract</x> Transcription factor E26 transformation-specific sequence-1 (ETS-1) is a transcription factor that regulates the expression of a variety of genes, including growth factors, chemokines, and adhesion molecules. We recently demonstrated that angiotensin II increases the glomerular expression of ETS-1 and that blockade of ETS-1 ameliorates the profibrotic and proinflammatory effects of angiotensin II. The Dahl salt-sensitive rat is a paradigm of salt-sensitive hypertension associated with local activation of the renin–angiotensin system. In these studies, we determined whether: (1) salt-sensitive hypertension is associated with renal expression of ETS-1 and (2) ETS-1 participates in the development of end-organ injury in salt-sensitive hypertension. Dahl salt-sensitive rats were fed a normal-salt diet (0.5% NaCl diet) or a high-salt diet (4% NaCl) for 4 weeks. Separate groups on high-salt diet received an ETS-1 dominant-negative peptide (10 mg/kg/d), an inactive ETS-1 mutant peptide (10 mg/kg/d), the angiotensin II type 1 receptor blocker candesartan (10 mg/kg/d), or the combination high-salt diet/dominant-negative peptide/angiotensin II type 1 receptor blocker for 4 weeks. High-salt diet rats had a significant increase in the glomerular expression of the phosphorylated ETS-1 that was prevented by angiotensin II type 1 receptor blocker. ETS-1 blockade reduced proteinuria, glomerular injury score, fibronectin expression, urinary transforming growth factor-β excretion, and macrophage infiltration. Angiotensin II type 1 receptor blocker reduced proteinuria, glomerular injury score, and macrophage infiltration, whereas concomitant ETS-1 blockade and angiotensin II type 1 receptor blocker had additive effects and reduced interstitial fibrosis. Our studies demonstrated that salt-sensitive hypertension results in increased glomerular expression of phosphorylated ETS-1 and suggested that ETS-1 plays an important role in the pathogenesis of end-organ injury in salt-sensitive hypertension.